2016
DOI: 10.1038/cddiscovery.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

PKC activation sensitizes basal-like breast cancer cell lines to Smac mimetics

Abstract: There is a need for novel strategies to initiate cancer cell death. One approach is the use of Smac mimetics, which antagonize inhibitor of apoptosis proteins (IAPs). Recent studies have shown that combinations of Smac mimetics such as LBW242 or LCL161 in combination with chemotherapeutic agents increase cancer cell death. Here we show that the protein kinase C (PKC) activator TPA together with the Smac mimetic LBW242 induces cell death in two basal breast cancer cell lines (MDA-MB-468 and BT-549) that are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It has been shown that combination treatment of Smac mimetic‐resistant basal breast cancer cell lines, including MDA‐MB‐468 and BT‐549 enhanced sensitivity to Smac mimetic in a TNFα‐dependent manner. However, non‐triple negative cells did not respond to this treatment strategy, which may be related to the intact production of TNF‐α following treatment or resistance to TNF‐α‐induced apoptosis . In another attempt to increase the efficacy of therapeutic approaches using Smac mimetics, addition of Smac mimetic TL32711 to combination of gemcitabine and the CHK1 inhibitor (AZD7762) led to significant cell cycle arrest and apoptosis induction in triple‐negative breast cancer cell lines .…”
Section: Application Of Smac Mimetics For Treatment Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that combination treatment of Smac mimetic‐resistant basal breast cancer cell lines, including MDA‐MB‐468 and BT‐549 enhanced sensitivity to Smac mimetic in a TNFα‐dependent manner. However, non‐triple negative cells did not respond to this treatment strategy, which may be related to the intact production of TNF‐α following treatment or resistance to TNF‐α‐induced apoptosis . In another attempt to increase the efficacy of therapeutic approaches using Smac mimetics, addition of Smac mimetic TL32711 to combination of gemcitabine and the CHK1 inhibitor (AZD7762) led to significant cell cycle arrest and apoptosis induction in triple‐negative breast cancer cell lines .…”
Section: Application Of Smac Mimetics For Treatment Of Breast Cancermentioning
confidence: 99%
“…However, non-triple negative cells did not respond to this treatment strategy, which may be related to the intact production of TNF-α following treatment or resistance to TNF-α-induced apoptosis. 82 In another attempt to increase the efficacy of therapeutic approaches using Smac mimetics, addition of Smac mimetic TL32711 to combination of gemcitabine and the CHK1 inhibitor (AZD7762) led to significant cell cycle arrest and apoptosis induction in triple-negative breast cancer cell lines. 83 Moreover, treatment of breast cancer cell lines MDA-MB-231 and MCF-7 with Smac mimetic LCL161 led to significant cell cycle arrest and induction of both apoptosis and necrosis, which was associated with cIAP1 degradation and accumulation of active RIP1.…”
Section: Birinapant As Single and Combinative Agentmentioning
confidence: 99%
“…For siRNA transfections, 500,000 cells per a 6 cm cell culture dish were seeded. Transfections were thereafter performed as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was performed as described [ 21 ]. Primary antibodies used were anti-actin (1:2000 MP Biomedicals C4), anti-caspase-8 (1:300 Cell Signaling #9746 and 1:300, Abcam ab32125), anti-caspase-3 (1:1000 Cell Signaling #9662), anti-caspase-7 (1:400 Cell Signaling #12827), anti-RIP1 (1:500 BD Biosciences 610458), anti-XIAP (1:400 BD Biosciences 610762), anti-cIAP1 (1:200 R&D Systems AF8181), anti-p100/p52 (1:500 Cell Signaling #4882) and anti-c-FLIP (1:400 Cell Signaling #5634).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Smac and Protein Kinase C delta (PKCδ) interact in basal-like and luminal breast cancer cells, but are dissociated after taxane cytotoxic treatment [183]. Further, activation of PKC synergizes with the Smac mimetic LBW242 in BLBC cell lines [184]. TRAIL agonists have been also shown to induce apoptosis of BLBC cells.…”
Section: Targeting Survival In Blbcmentioning
confidence: 99%